INFLUENCE OF FINANCIAL RATIO ON PROFIT GROWTH (EMPIRICAL STUDY OF FOOD AND BEVERAGE MANUFACTURING COMPANIES LISTED IN THE INDONESIAN SHARIA STOCK INDEX (ISSI) 2014-2020) - Hayatun Solihat; Novi Mubyarto; Mohammad Orinaldi (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to determine the effect of financial ratios on profit growth in the manufacturing sub-sectors of food and beverages listed in the stock index Indonesian sharia (ISSI) in the period 2014-2020 partially and simultaneously. The population in this study is a manufacturing company in the food and beverage sub-sector obtained by purposive sampling technique. The data analysis method used is panel data regression analysis using software tools eviews 10. The results show that the variables Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Net Profit Margin (NPM) simultaneously affect profit growth. While the CR, DER, and NPM variables partially affect profit growth, the TAT variable does not affect the profit growth of food and beverage manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2014-2020 period.